(untitled) (Bangladesh Journal of Animal Science, 2015)
Four different types of rasomalai were prepared from cow milk chhana (acid curd) with the addition of different levels of soy chhana. The prepared rasomalai were named as A (100% cow milk chhana), B (75% cow milk chhana+25% Soy Chhana), C (50% cow milk chhana+50% soy chhana) and D (25% cow milk chhana+75% soy chhana). The qualities of prepared rasomalai were evaluated by using physical and chemical parameters. It was observed that the addition of soy chhana with cow milk chhana decreased the organoleptic score of the prepared rasomalai. The moisture, total solids and carbohydrate content of the sample were not significantly differed, but protein (p<0.05), ash (p<0.05), fat (p<0.01) content and acidity percent (p<0.01) of the samples were significantly decreased in addition of soy chhana with cow milk chhana. Considering the physico-chemical properties of all samples, it was found that most suitable and acceptable quality of rasomalai can be prepared by admixture of 25% soy chhana and 75% cow milk chhana. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23144 Bang. J. Anim. Sci. 2014. 44 (1): 59-63